(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This study investigates the knowledge levels of statistical modelling among students in Tertiary Education in Anambra State, Nigeria, highlighting significant variances in comprehension and engagement. A convenience sample of one hundred and forty-eight (n = 122) first-year undergraduates comprising 71 females (65.5%) and 51 males (34.5%) aged 16 to 28 years old participated in the study. The data reveals that a large proportion of students fall within the low (39.34%) and very low (20.49%) knowledge categories, while only a small fraction demonstrates high (11.48%) or very high (7.38%) proficiency. These findings underscore the critical need for enhanced educational strategies to improve students' understanding of statistical modelling. The implications suggest that students can apply statistical concepts in real-world scenarios with targeted interventions, impacting their academic and professional success. This study provides a foundation for further exploration into improving statistical education in Nigeria, ensuring students are better equipped to meet academic and professional demands.